Perbandingan Hasil Pemeriksaan HBsAg dan Anti-HIV Reaktif Metode ChLIA di Palang Merah Indonesia Kota Yogyakarta - Nadia Nanda Safitri; Nazula Rahma Shafriani; Arif Yusuf Wicaksana (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Examination for Infections Transmitted through Blood Transfusion (IMLTD) includes the identification of Hepatitis B surface Antigen (HBsAg) and antiHIV. One way to check HBsAg and anti-HIV can be done using the Chemiluminescence Immuno Assay (ChLIA) method. This study aims to analyze the comparison of HBsAg and antiHIV reactive examination results using the ChLIA method at PMI (Indonesian Red Cross) in Yogyakarta City. The method used was secondary data collection in 2020-2022. Data analysis was done using the Kruskal Wallis test. The results of the statistical analysis of the HBsAg examination showed a p value of 0.041, which means that there were differences in the levels of reactive HBsAg examination results using the ChLIA method. Then the results of the statistical analysis of the anti-HIV examination showed a p value of 0.967, which means there was no difference in the levels of reactive anti-HIV examination results using the ChLIA method. The results revealed donor HBsAg and anti-HIV reactive examinations based on the characteristics of the majority was male, the majority was adult (20-54 years), most blood types was type O, all were rhesus positive, the majority of jobs was other categories for reactive HBsAg, and employees/employee for anti-HIV reactive.